«L’età d’oro della Vita». La vecchiaia di Oriana Fallaci - Tichoniuk-Wawrowicz, Ewa (Studia Romanica Posnaniensia, 2018)
From Tithonus to the Struldbrugs of Swift, the old age is seen as a phase of decline, of decay, of exclusion from active life, which generates conditions of need. Senility can become even an influencing discrimination: in 1969 Robert Butler coined the term ageism and developed the theory of the phenomenon. So it is very surprising to see the optimism of Oriana Fallaci who observed: «They are fools those who refuse [the old age] and in order to refuse it they make the facelift, they dress up like a twenty-yearold, they cheat on age. Silly and ungrateful. […] The oldness is a beautiful age. The golden age of Life» [IA 149-150]. The tone marvels even more if you think about the cancer against which the Florentine journalist fought for years. It therefore seems interesting to analyze the reason for such serenity, despite the thanatic shadow.